Implementing Child-Friendly Tourism by a Concept of Edutourism to Enhance Village Economic Growth - Anang Kistyanto; Febrika Yogie Hermanto; Amirusholihin; Ina Uswatun Nihaya; Zulfin Rachma Mufidah (International Journal of Community Service Learning, 2025)
Management of Edutourism targeting children is a significant concern for providing child-friendly learning places. With child-friendly Edutourism management, it is hoped that tourist visitors can increase significantly in line with the needs of child-friendly tourism. The purpose of this Community Service (PKM) activity is to assist BUMDES Sejahtera Ponokawan in the Dewi Kenangan Edutourism sub-business by implementing the Edutourism Management Model with the Child-Friendly Edutainment Principle. The implementation method of this PKM adopts the research and development (RnD) method - 5 stages in the ADDIE model and is based on Asset Based Community Development (ABCD). Participants in this PKM are the managers of Dewi Kenangan Edutourism, Dewi Kenangan Edutourism instructors, and the Management of BUMDES Sejahtera Ponokawan. Data analysis in this PKM uses qualitative data analysis on interview data, observations, and focus group discussions, as well as quantitative data analysis on pretest, posttest, and N-Gain score data. The results of this PKM show that the model can be implemented well by the managers of Dewi Kenangan Eduwisata, the instructors of Dewi Kenangan Eduwisata, and the Management of BUMDES Sejahtera Ponokawan. Mentoring was carried out effectively in the preparation, opening (launching), and implementation of the tourism model in Dewi Kenangan Eduwisata. The positive response from the managers of Dewi Kenangan Eduwisata, the instructors of Dewi Kenangan Eduwisata, and the Management of BUMDES Sejahtera Ponokawan to the model that was implemented to increase economic growth in Ponokawan Village. Thus, this program was declared successful because it had a positive impact on business development and expansion in Eduwisata.